Ultrasound guided microwave ablation of thyroid nodular goiter and cystadenoma: A single center, large cohort study. Issue 34 (27th August 2021) - Honglei, Gao; Shahbaz, Muhammad; Farhaj, Zeeshan; Ijaz, Muhammad; Kai, Sun Yu; Davrieux, Carlos Federico; Cheng, Sun Zuo
Abstract : Abstract: Thyroid nodules are one of the most common entities that affect the thyroid gland. Traditionally, their treatment was surgery. Currently, ablation combination with percutaneous procedure became a good option. To analyze safety, efficacy, and describe our experience in microwave-ablation using ultrasound-guidance for benign thyroid nodules. A total of 304 patients with 1180 thyroid nodules (thyroid cystadenoma and nodular goiter) were studied retrospectively. Two hundred sixty-seven patients who underwent microwave-ablation successfully in our hospital were enrolled in this study. The baseline, follow-up nodule volume, thyroid function tests, thyroid antibodies, and posttherapy complications were analyzed. The informed written consent was obtained from patients or guardians. The study was approved by the ethics committee of our hospital. The average age was 50.1 ± 11.7 (21–83 years), 214 were women (80.1%) and 53 (19.9%) were men. The average number of nodules per patient was 4.02 ± 1.8 (1–8), 9.86%, 6.13%, and 84% located in the right thyroid lobe, left lobe, and bilateral, respectively. The average size of the nodules was 5.28 cm 2  ± 3.63 (0.09–23.45 cm 2 ). The average ablation time was 11 minutes ± 5.36 (3–20 minutes). The hospitalization period was 24 hours ± 10.16 (7–48 hours). Eighteen complications were reported. Postablation volume reduction rate was 54.74% and 93.3% at 3 and 12 months follow-up respectively ( P  < .05). The thyroid function tests, pre and postablation showed no significant changes ( P  > .05). Ultrasound-guided microwave-ablation of thyroid nodules is safe and effective. More clinical trials are needed to define the true use of microwave-ablation.